2014
DOI: 10.1016/j.jbtep.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Verbal worry facilitates attention to threat in high-worriers

Abstract: Background and objectivesWorry is predominantly a verbal-linguistic process with relatively little imagery. This study investigated whether the verbal nature of worry contributes to the maintenance of worry by enhancing attention to threat. It was hypothesised that verbal worry would lead to greater attentional bias to threat than imagery-based worry.MethodsFifty high-worriers were randomly assigned to one of two groups, one in which they were instructed to worry in a verbal way and one in which they worried i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 22 publications
4
49
0
1
Order By: Relevance
“…Interestingly, previous studies already emphasized that worry induction could influence specific cognitive functions or processes such as attention orienting towards threat-related stimuli (Oathes et al, 2010;Williams et al, 2014), however in individuals that already had high levels of trait worry or were prone to worry, respectively, confirming a role of more stable trait dispositions (or interactions between state and 37 trait factors) in the case of worry in its propensity to interfere with cognitive processes. Accordingly, our new behavioral results are compatible with this interpretation, but they also extend these earlier findings by showing that trait, but not state worry, can influence early and automatic action monitoring processes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, previous studies already emphasized that worry induction could influence specific cognitive functions or processes such as attention orienting towards threat-related stimuli (Oathes et al, 2010;Williams et al, 2014), however in individuals that already had high levels of trait worry or were prone to worry, respectively, confirming a role of more stable trait dispositions (or interactions between state and 37 trait factors) in the case of worry in its propensity to interfere with cognitive processes. Accordingly, our new behavioral results are compatible with this interpretation, but they also extend these earlier findings by showing that trait, but not state worry, can influence early and automatic action monitoring processes.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, Williams, Mathews, and Hirsch (2014) pointed out that worry manipulations (and therefore state worry) can have deleterious effects on cognitive functions such as attention.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, she attempts to adjust her worry based on ongoing expectations about the occurrence of a potential threat. Worry tends to have a more verbal rather than visual manifestation, and individuals with GAD report less concrete descriptions of major worries relative to control participants (Leigh & Hirsch, ; Stöber & Borkovec, ; Williams, Mathews, & Hirsch, ). Given that the future is inherently uncertain, highly concretized worries may be a less efficient solution for enabling management of unexpected contingencies when they do arise, insofar as the occurrence of a threatening event may differ substantially from one's expectations.…”
Section: Anxiety Disorder Subtypesmentioning
confidence: 99%
“…Studies show that worry is predominantly a verbal process, and that it is the verbal form of worry, rather than imagery-based worry, which depletes working memory and enhances attention to threatening information (Hayes, Hirsch, & Mathews, 2008;Leigh & Hirsch, 2011;Rapee, 1993;Williams, Mathews, & Hirsch, 2014). Demonstrating a clear relationship between verbal processes and worry, Engels et al (2007) found that worry was associated with greater activity in the left inferior frontal gyrus-an area involved in subvocal articulatory rehearsal and maintenance of verbal information (Awh et al, 1996;Fletcher & Henson, 2001;Zatorre, Meyer, Gjedde, & Evans, 1996).…”
mentioning
confidence: 99%